A tupaia paramyxovirus vector system for targeting and transgene expression - Engeland, Christine Elisabeth; Bossow, Sascha; Hoyler, Birgit; Derani, Judith; Veinalde, Rūta; Jäger, Dirk; Ungerechts, Guy; Springfeld, Christoph (Journal of general virology, 2017)
Viruses from the diverse family of Paramyxoviridae include important pathogens and are applied in gene therapy and for cancer treatment. The Tupaia paramyxovirus (TPMV), isolated from the kidney of a tree shrew, does not infect human cells and neutralizing antibodies against other Paramyxoviridae do not cross-react with TPMV. Here, we present a vector system for de novo generation of infectious TPMV that allows for insertion of additional genes as well as targeting using antibody single-chain variable fragments. We show that the recombinant TPMV specifically infect cells expressing the targeted receptor and replicate in human cells. This vector system provides a valuable tool for both basic research and therapeutic applications.